Limitations of the International HIV Dementia Scale in the current era. (13th November 2018) - Milanini, Benedetta; Paul, Robert; Bahemana, Emmanuel; Adamu, Yakubu; Kiweewa, Francis; Langat, Rither; Owuoth, John; Allen, Elaine; Polyak, Christina; Ake, Julie; Valcour, Victor
Abstract : Objective: The International HIV Dementia Scale (IHDS) was developed as a tool to detect HIV-dementia in both industrialized and resource-limited settings. Studies employing the IHDS have produced mixed results, with recent data suggesting unusually high rates of dementia among Ugandans. This study aimed to define the performance characteristics of the IHDS in three African countries. Design: Cross-sectional study. Methods: We recruited 2208 HIV-infected and 429 HIV-uninfected individuals from East Africa (Kenya n  = 1384; Tanzania n  = 368; Uganda n  = 456) who underwent testing with the IHDS and a 30-min neuropsychological testing battery. Cognitive impairment was defined as −1SD on two of six tests or −2SD on one test compared with demographically matched controls stratified by age and education. We examined predictive capacity of the IHDS to detect cognitive impairment using receiver-operator characteristic (ROC) curve analysis. Results: The mean (SD) ages of the HIV-infected and HIV-uninfected groups were 39.7 (10.7) and 37.4 (10.4), respectively. Among HIV-infected individuals, 1508 (68%) were on combination antiretroviral therapy (cART), 1298 (61%) had plasma viral load less than 500 copies/ml and 884 (38%) met criteria for cognitive impairment. Using the customary IHDS cut-off of 10, 1136 (83%) of the HIV-infected participants met criteria for dementia resulting in 91% sensitivity but only 17% specificity. A modified cut-off score of 8 derived from the ROC resulted in low sensitivity (56%) and specificity (64%). Conclusion: The IHDS has poor performance characteristics for the identification of cognitive impairment in East Africa. Cultural-informed and sensitive screening tests are needed to detect mild cognitive dysfunctions in developing countries.